Effect of NaCl Electrolyte Concentration on Al2O3 nanoparticle synthesis by electrochemical methods - Maria Magdalena Kolo; Fredy Kurniawan (Jurnal Kimia Terapan Indonesia, 2020)
The Synthesis of Aluminum Oxide Nanoparticles with the electrochemical Method has been investigated. The electrochemical cell consists of a cathode (Al) and anode (Al), then a solution of NaCl as the electrolyte. The variation of the concentration of electrolytes used in this study i.e, 0.1 M; 0.2 M; 0.3 M; 0.4 M and 0.5 M. The reaction was conducted for 15 minutes until the color changes from colorless solution become cloudy. Particle size analysis of alumina nanoparticles using a Zetasizer instrument. The results of particle size analysis of the effect of variations in NaCl solution were used for each concentration of 0.1 M - 0.5 M which is 96.2 nm; 107.4 nm; 120.1 nm; 125.8 nm and 211.0 nm respectively. X-ray Diffraction (XRD) and particle size analysis were used to characterize the structure and size of the product. Î³- Al2O3 nanoparticles were obtained by this method. The result showed the alumina nanoparticle size increases with electrolyte concentration